Premature labor and neonatal sepsis caused by Actinomyces neuii - Fahad Alsohime; Rasha A. Assiri; Fatimah Al-Shahrani; Hind Bakeet; Malak Elhazmi; Ali M. Somily (Elsevier, 2019)
Actinomycosis is a rare infection in patients younger than 10 years of age. It mainly affects the cervicofacial region, but many other sites of infection have been recognized. About 70% of infections are due to either Actinomyces israelii or Actinomyces gerencseriae.Actinomyces neuii was first described in 1985 in two patients with post cataract endophthalmitis, A. neuii represents 17% of clinical Actinomyces isolates. Several reports indicated a well-known association between Actinomyces infections and Intrauterine devices (IUD).We are reporting a case of neonatal sepsis due to A. neuii as a first case reported from Saudi Arabia. It was thought to be the cause of the premature labor and neonatal sepsis.The prevalence of Actinomyces infection is likely underestimated and additional premature labors and abortions could have been caused by Actinomyces infections that were never detected. More studies are needed to confirm the association of maternal Actinomyces infections with preterm labor. Keywords: Actinomyces neuii, Newborn, Sepsis